I Balcani occidentali tra romanico e bizantino Tradizione e sperimentazione nell'architettura serba della seconda metà del XII secolo - Filipović, Aleksandra (Europe in between. Histories, cultures and languages from Central Europe to the Eurasian Steppes, 2020)
This volume focuses on the ecclesiastical architecture of 12th-century Nemaniad origins (Mother of God, Saint Nicholas and Saint George) by examining the layout preferences of the client and the workforce of diverse cultural backgrounds. The author discusses the monuments' construction techniques as a primary instrument for shaping space by taking into consideration the visual effects of the domed space of Romanesque architecture as diametrically opposed to architectural elements present in the Byzantine world. The analysis of the different construction phases of the churches considered is carried out based on archival documents, on a survey carried out in the field, and a reconstruction of their realities within a historical context. What emerges in this analysis is that a regional architecture's selection choices for construction should not be understood as an either-or scenario between Byzantium and the West, but rather as the result of a synthesis of different local architectural traditions that comes to fruition in Medieval Serbia.